Note on the deck transformations group and the monodromy group - Żołądek, Henryk (Topological Methods in Nonlinear Analysis, 2002)
For a ramified covering between Riemann surfaces the groups Deck of deck transformations and Mon of monodromy permutations are introduced. We associate with them groups of automorphisms of certain extensions of function fields. We study relations between these objects.